The The Relationship Between Physical Fitness Level and Basketball Performance Among Students of Sman 4 Bandung City: Hubungan Tingkat Kebugaran Jasmani Dengan Penampilan Bermain Bola Basket Pada Siswa Sman 4 Kota Bandung - Agi Firmansyah; Sucipto Sucipto; Reshandi Nugraha (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan Undiksha, 2025)
This study aims to analyze the relationship between physical fitness levels and basketball performance among students participating in extracurricular activities at SMAN 4 Kota Bandung. Physical fitness plays a crucial role in enhancing athletic performance, and this study focuses on how fitness levels influence basketball skills. The research method employed is a quantitative approach using a one-shot case study design. The research sample consisted of 60 students who actively participated in basketball extracurricular activities. Physical fitness data was measured using the Indonesian Physical Fitness Test (TKJI), which includes several physical components such as running, body lifting, and endurance, while performance was measured using the Game Performance Assessment Instrument (GPAI), which evaluates technical skills and game strategy. The results showed that most students were in the “adequate” physical fitness category, while their playing performance was in the “poor” category. Correlation analysis using Pearson's coefficient revealed a significant positive relationship (r = 0.366, p < 0.047) between physical fitness levels and basketball playing performance among female students. Furthermore, Pearson's correlation coefficient analysis revealed a significant positive correlation (r = 0.401, p < 0.028) between physical fitness levels and basketball performance among male students. This indicates that students with better physical fitness tend to demonstrate better playing skills, which can directly impact success on the court.